Discovery and optimization of substituted oxalamides as novel heme-displacing IDO1 inhibitors. (1st February 2021) - Steeneck, Christoph; Kinzel, Olaf; Anderhub, Simon; Hornberger, Martin; Pinto, Sheena; Morschhaeuser, Barbara; Albers, Michael; Sonnek, Christina; Czekańska, Marta; Hoffmann, Thomas
Graphical abstract: Abstract: Since the advent of antibody checkpoint inhibitors as highly efficient drugs for cancer treatment, the development of immunomodulating small molecules in oncology has gained great attention. Drug candidates targeting IDO1, a key enzyme in tryptophan metabolism, are currently under clinical investigation in combination with PD-1/PD-L1 agents as well as with other established anti-tumor therapeutics. A ligand based design approach from hydroxyamidine 4 that aimed at heme-binding IDO1 inhibitors resulted in new compounds with moderate IDO1 potency. A hybrid structure design that made use of the linrodostat structure (2 ) led to oxalamide derived, heme-displacing IDO1 inhibitors with high cell-based IDO1 potency and a favorable ADME/PK profile.